(untitled) (Journal of the College of Basic Education, 2025)
The art of the postmodern era announced its abandonment of all values، including artistic and aesthetic values، and its separation from the pattern of history through its embodiment of contents and forms characterized by distortion and strangeness that are in harmony with the state of cognitive openness characterized by freedom from rational observation of the entire postmodern system، and its attachment to the vulgar، the marginal، the everyday، and the emergency. Which is consistent with the aspirations that reject elite art، reinforcing the concepts of irrationality، nihilism، deconstruction، and difference، as postmodern art is based on attracting the mind and attention of the recipient، not his eyes and feelings، to form a kind of spiritual alienation in the relationship of the self to nature. Thus، this research addresses the problem of reaching a new world that has dropped all standards، The importance of the research is evident through the widening scope of research between values and the post-modern era and the study of the era with all its ramifications and its reflection on the aesthetic، technical and artistic aspects. Its results benefit those interested، as the research has historical، aesthetic and artistic importance based on the descriptive and analytical approaches، The research plan is divided into an introduction، two sections، and a conclusion. In the first section، the researcher investigates the art schools throughout the most widespread and widespread post-modern era، and penetrates them into all the experiences، techniques، and procedures of these art schools. In the second section، she addresses the artists who most express the vocabulary of (value subversion) and its trends with an objective vision. It is closer to the spirit of monitoring and analysis، and the conclusion includes the most prominent conclusions and recommendations reached.